2012
DOI: 10.1371/journal.pone.0039905
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Microbial Signatures of the Endemic Marine Sponge Arenosclera brasiliensis

Abstract: The endemic marine sponge Arenosclera brasiliensis (Porifera, Demospongiae, Haplosclerida) is a known source of secondary metabolites such as arenosclerins A-C. In the present study, we established the composition of the A. brasiliensis microbiome and the metabolic pathways associated with this community. We used 454 shotgun pyrosequencing to generate approximately 640,000 high-quality sponge-derived sequences (∼150 Mb). Clustering analysis including sponge, seawater and twenty-three other metagenomes derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 53 publications
2
51
0
2
Order By: Relevance
“…The production of manzamine A, an alkaloid found in several haplosclerid sponges, has been assigned to an Actinomycetales strain of the genus Micromonospora (12). Furthermore, our previous metagenomic analysis indicated that Actinobacteria was one of the most abundant bacterial phyla in the microbiome associated with A. brasiliensis (29). Therefore, it is reasonable to suggest that A. brasiliensis-associated Actinobacteria communities might be responsible for the production of secondary metabolites as well as of bioactive polyketides.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The production of manzamine A, an alkaloid found in several haplosclerid sponges, has been assigned to an Actinomycetales strain of the genus Micromonospora (12). Furthermore, our previous metagenomic analysis indicated that Actinobacteria was one of the most abundant bacterial phyla in the microbiome associated with A. brasiliensis (29). Therefore, it is reasonable to suggest that A. brasiliensis-associated Actinobacteria communities might be responsible for the production of secondary metabolites as well as of bioactive polyketides.…”
Section: Resultsmentioning
confidence: 96%
“…Specimens of A. brasiliensis were collected at João Fernandinho's Beach, which is located in the Búzios peninsula in the state of Rio de Janeiro (22°44=49==/41°52=54==W), during two expeditions in May 2010 and January 2011. Sponge specimens were transported under controlled temperature (24°C) in aerated seawater for approximately 3 h and then washed and processed for total DNA extraction exactly as previously described (29). Briefly, samples were set on sterile seawater for 5 to 10 min, dissected with a sterile scalpel, dried by gently pressing on sterile paper towels, and ground in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While complete genome sequencing gives us detailed knowledge about a single prokaryotic species, metagenomic sequencing gives as a broad overview of the microbial environment (Dinsdale et al, 2008). Whether analyzing genomic or metagenomic sequencing, one of the main goals is to identify the taxonomic origin of species or species (Belda-Ferre et al, 2012;Mande, Mohammed, & Ghosh, 2012;Trindade-Silva et al, 2012;Carr, Shen-Orr, & Borenstein, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While complete genome sequencing gives us detailed knowledge about a single prokaryotic species, metagenomic sequencing gives as a broad overview of the microbial environment (Dinsdale et al, 2008). Whether analyzing genomic or metagenomic sequencing, one of the main goals is to identify the taxonomic origin of species or species (Belda-Ferre et al, 2012;Mande, Mohammed, & Ghosh, 2012;Trindade-Silva et al, 2012;Carr, Shen-Orr, & Borenstein, 2013).There are two typical approaches to identifying the species present in a metagenome. The most common methods use homology searches against a reference database of known taxonomic lineage (Altschul et al, 1997;Meyer et al, 2008;Segata et al, 2012).…”
mentioning
confidence: 99%